Whole Genome Sequence Analysis to Identify SARS-CoV-2 Variant in Nepal - Shrestha, R.; Katuwal, N.; Adhikari, N.; Vanaerschot, M.; Tamrakar, D.; Dhimal, M.; Gyanwali, P.; Bhattarai, S.; Madhup, S. K.; Devkota, B. (Kathmandu University Medical Journal, 2021)
Background The spread of SARS-CoV-2 has become a global public health crisis. Nepal is facing the second wave of COVID-19 pandemic but, there is still a limited data on the genomic sequence of SARS-CoV-2 variants circulating in Nepal. Objective The objective of this study is to sequence the whole genome of SARS-CoV-2 in Nepal to detect possible mutation profiles and phylogenetic lineages of circulating SARSCoV- 2 variants. Method In this study, swab samples tested positive for SARS-CoV-2 were investigated. After RNA extraction, the investigation was performed through real-time PCR followed by whole genome sequencing. The consensus genome sequences were, then, analyzed with appropriate bioinformatics tools. Result Sequence analysis of two SARS-CoV-2 genomes from patient without travel history (Patient A1 and A2) were found to be of lineage B.1.1. Similarly, among other four samples from subjects returning from the United Kingdom, genomes of two samples were of lineage B.1.36, and the other two were of lineage B.1.1.7 (Alpha Variant). The mutations in the consensus genomes contained the defining mutations of the respective lineages of SARS-CoV-2. Conclusion We confirmed two genomic sequences of variant of concern VOC-202012/01 in Nepal. Our study provides the concise genomic evidence for spread of different lineages of SARS-CoV-2 – B.1.1, B.1.36 and B.1.1.7 of SARS-CoV-2 in Nepal.